Local Kinematics and the Local Standard of Rest - Schoenrich, R; Binney, J; Dehnen, W (2009)
We re-examine the stellar kinematics of the Solar neighbourhood in terms of the velocity of the Sun with respect to the local standard of rest. We show that the classical determination of its component V_sun in the direction of Galactic rotation via Stroemberg's relation is undermined by the metallicity gradient in the disc, which introduces a correlation between the colour of a group of stars and the radial gradients of its properties. Comparing the local stellar kinematics to a chemodynamical model which accounts for these effects, we obtain (U,V,W)_sun = (11.1 +/- 0.74, 12.24 +/- 0.47, 7.25 +/-0.37) km/s, with additional systematic uncertainties of ~ (1,2,0.5) km/s. In particular, V_sun is 7 km/s larger than previously estimated. The new values of solar motion are extremely insensitive to the metallicity gradient within the disc.